PENGARUH MODEL PEMBELAJARAN COOPERATIVE SCRIPT TERHADAP HASIL BELAJAR IPA TERPADU SISWA KELAS VIII SMPN 10 MERANGIN TAHUN PELAJARAN 2019/2020 - Wika Wirianti; Arista Ratih; Eko Wulandari (Pendidikan Biologi STKIP YPM Bangko, 2019)
Based on observations made by researchers found that learning in class VIII SMPN 10 Merangin there are students who pay less attention to the material delivered by the teacher, disturbing friends and busy talking with the theme, learning also feels monotonous because teachers still use the lecture method in the teaching and learning process. This has an impact on the results of the Integrated Science test in the last semester and the average of all classes does not reach the Minimum Mastery Criteria value of 75, therefore through this study the researcher wants to know the effect of the Cooperative Script learning model on students' Integrated Science learning outcomes class VIII SMPN 10 Merangin on straight motion material. In this study, researchers used experimental quantitative research because researchers wanted to find out the effect of Cooperative Script learning models on the learning outcomes of Integrated Science students in grade VIII of SMP Negeri 10 Merangin. The population in this study were all students of class VIII of SMPN 10 Merangin consisting of seven classes, from classes VIII A, VIII B, VIII C, VIII D, VIII E, VIII F, and VIII G, totaling 208 students. In determining the sample, the researcher first tests the normality and homogeneity tests of the population. Then from the population data obtained 21 combinations, then the draw was made so that a pair of combinations was chosen, namely DG which means class VIII D as the control class and class VIIIG as the experimental class. Data collection techniques are done using tests. To analyze the test items, researchers used validity tests, distinguishing features, difficulty indexes, and reliability tests. Based on the analysis of this data obtained from the t test where sig of 0.63 where> 0.05. From the results of this study, it can be concluded that there is an effect of the Cooperative Script learning model on the Integrated Science learning outcomes of Grade VIII students of SMPN 10 Merangin.